2019
DOI: 10.1371/journal.pone.0216947
|View full text |Cite
|
Sign up to set email alerts
|

Selected serum microRNA, abdominal aortic calcification and risk of osteoporotic fracture

Abstract: Context MicroRNA (miRNA) regulate post-transcriptionally the expression of osteogenesis and angiogenesis associated genes and emerge as potential non-invasive biomarkers in vascular and bone diseases. Severe abdominal aortic calcification (AAC) is associated with higher risk of cardiovascular event and of fragility fracture. Objective To identify miRNA linked to the aggravation of AAC and to incident osteoporotic fracture. Design Postmenopaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 56 publications
(71 reference statements)
0
15
0
Order By: Relevance
“…None of the three selected miRs (miR-26a-5p, miR-34a-5p, and miR-223-5p) by Pickering et al [67] showed significant differences in the serum of PM OP wF patients when compared to woF PM CTRs.…”
Section: Op Wf Vs Ctr Wofmentioning
confidence: 85%
“…None of the three selected miRs (miR-26a-5p, miR-34a-5p, and miR-223-5p) by Pickering et al [67] showed significant differences in the serum of PM OP wF patients when compared to woF PM CTRs.…”
Section: Op Wf Vs Ctr Wofmentioning
confidence: 85%
“…Pickering et al [ 64 ] examined the miRNA expression levels between 217 OP patients with fragility fractures and 217 HC without a history of fragility fractures, in addition to making an assessment of the same serum miRNAs in 183 women with abdominal aortic calcification (AAC). Three miRNAs (miR-26a-5p, miR-34-5p, and miR-223-5p) were selected from predictive programs (i.e., TargetScan, MiRWalk database), according to their relevance in vascular calcification and bone metabolism, and assayed by qPCR.…”
Section: Circulating Mirnas As Potential Biomarkers In Bone Fragilmentioning
confidence: 99%
“…On the other hand, Pickering et al reported that serum miR-26a, miR-34a, and miR-223 did not differ between those with and without VC progression [77], findings that are in contrast to those by Cavallari et al, who described that plasma miR-223 increased in those with ESRD under chronic dialysis [49]. It is likely that the numbers of subjects being tested, the timing of the assay for circulatory miRNAs, the controls used to derive miRNA data, and the biologic fluid assayed may account for the discrepancy we observed.…”
Section: Discrepancies Between Calcified and Non-calcified Tissues Ormentioning
confidence: 97%
“…Interestingly, most reports (n = 40; 60.6%) looked into the pathogenic role of non-coding RNA in VC, while histone modification (n = 6; 9.1%) [53][54][55][56][57][58], DNA methylation (n = 8; 12.1%) [5,[59][60][61][62][63][64][65], and chromatin changes (n = 3; 4.5%) [66][67][68] accounted for one-fourth only. Nine (13.6%) [69][70][71][72][73][74][75][76][77] examined the discrepancy of epigenetic signatures between subjects or animals with and without VC but not their pathogenic influences. In the following sections, we summarize results from these reports and try to synthesize an inter-connected network of epigenetic regulation of VC based on the existing data assisted by bioinformatic integration.…”
Section: Strategy Of Literature Review and Findingsmentioning
confidence: 99%
See 1 more Smart Citation